Assessment of serum zinc, selenium, and prolactin concentrations in critically ill children - Negm FF; Soliman DR; Ahmed ES; Elmasry RA (Dove Medical Press, 2016)
Farida F Negm,1 Doaa R Soliman,1 Enas S Ahmed,2 Rasha A Elmasry1 1Department of Pediatrics, 2Department of Clinical Pathology, Faculty of Medicine, Benha University, El-Kalyobia, Banha, Egypt Background: In critically ill patients, there are reduced stores of antioxidants, which are associated with increased organ failure and even higher mortality. Trace elements, especially zinc and selenium, are the cornerstone of the antioxidant defense in acute systemic inflammatory response syndrome. Prolactin (PRL) is the counterregulatory stress hormone that prevents cortisol/stress-induced lymphocyte apoptosis. The aim of our study is to detect the serum levels of zinc, selenium, and PRL hormone as important immunomodulators in critically ill children and to investigate the relationship between these immunomodulators and the severity of illness. Subjects and methods: This was a prospective study that included two groups; group 1: 50 critically ill children within 72 hours of intensive care unit admission, and group 2: 30 healthy children as controls. Blood samples were collected from the two groups for zinc, selenium, and PRL level measurement. Results: Zinc and PRL levels were found to be decreased in critically ill children compared to control group, and these levels were inversely correlated with organ failure index and pediatric logistic organ dysfunction scores. Selenium levels were decreased in patients with sepsis and in patients with multiple organ failure. Conclusion: Serum concentrations of zinc and PRL are generally low in critically ill children, with a greater decrease in patients with sepsis and in the presence of multiple organ failure. The levels of zinc and PRL are inversely correlated with severity of illness. Selenium levels were decreased in patients with sepsis and in patients with multiple organ failure. Keywords: critically ill, intensive care, zinc, selenium, prolactin